Peningkatan Kompetensi Pamong SMK Tamansiswa Banjarnegara Melalui Pemanfaatan Internet Produktif dalam Pembelajaran - Nurchim, Nurchim; Suryadi, Agung (LPPM Universitas Duta Bangsa Surakarta, 2022)
Recently, there has been an increase in the use of the internet in the educational environment. Internet-based learning, known as online learning, is an alternative to acquiring appropriate knowledge and skills so as to encourage students to be able to study outside class hours. However, not all teachers have adequate digital literacy. The use of the internet in learning tends to be just a search for information to support learning and even entertainment. This community service activity aims to improve the competence of teachers at SMK Tamansiswa Banjarnegara in using the internet productively in learning. The activities are carried out face-to-face in the form of lectures and discussions with them. The discussion of the material includes internet basics, internet-based learning strategies and the introduction of online applications that support vocational learning. After the implementation of this activity, it is hoped that the teachers will gain new knowledge and insights as an increase in teaching competence to students by using the internet.